VD_FINDINFO Décision / 2024 / 1 vom 28. Dezember 2023 - VD Tribunal cantonal (2023)
REJET DE LA DEMANDE, DÉTENTION PROVISOIRE | 221 al. 1 let. c CPP (CH), 221 al. 2 CPP (CH), 222 CPP (CH), 237 CPP (CH), 393 al. 1 let. c CPP (CH)